Reveille : Poems - Clark, George David (Book collections on Project MUSE., 2015)
In Reveille, a man suffers fits of super-natural coughing, flytraps attack a child, a moray haunts a waterbed, poltergeists revise a church's furnishings, an interview is conducted through a man-eater's throat, and the prodigal son stalks his local brothel in a pair of lion hide pajamas. The copious invention in these poems renders a host of holy objects and exotic creatures, surveying them the way one might the emblems in a dream: curious of their meanings but reluctant to interpret them and simplify their mystery. Theologically playful, rhetorically sophisticated, and formally ambitious, Reveille is rooted in imaginative awe and driven by the impulse to praise. At its heart this is a book of love poems, though its loves are varied and complicated by terrible threats: that the cradle will break, that we will cry out and not be answered, and that we will fall asleep and never wake. Against such jeopardy these poems fix our attention on the horizon: "Listen: that's your singular name / unfurling through the whisper-weight trumpets of light." Morning comes and Reveille calls forth a team of baton twirlers on roller skates, pamphlets announcing new flavors of ice cream, caravans of camels hauling bolts of velvet, fragrant monuments to rapture."--Inside front cover.